(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2014)
Based upon fieldwork in Italy and the USA, the authors present work-in-progress insights into solidarity economies, and in particular alternative food networks, as a form of active citizenship that could re-orient the current debate on responsible innovation.